The Pharmacology of Acute Lung Injury in Sepsis - Brian Michael Varisco (Advances in Pharmacological Sciences)
Acute lung injury (ALI) secondary to sepsis is one of the leading causes of death in sepsis. As such, many pharmacologic and nonpharmacologic strategies have been employed to attenuate its course. Very few of these strategies have proven beneficial. In this paper, we discuss the epidemiology and pathophysiology of ALI, commonly employed pharmacologic and nonpharmacologic treatments, and innovative therapeutic modalities that will likely be the focus of future trials.